2020
DOI: 10.1002/asna.202013791
|View full text |Cite
|
Sign up to set email alerts
|

Solar observatory Einstein Tower: Data release of the digitized solar full‐disk photographic plate archive

Abstract: We present solar full‐disk observations that were recorded at the Einstein Tower during the years 1943–1991 (solar cycles 18–22). High‐school students from Potsdam and Berlin digitized more than 3,500 full‐disk images during 2–3‐week internships at Leibniz‐Institut für Astrophysik Potsdam (AIP). The digital images cover a 15 cm × 15 cm region on photographic plates, which were scanned at a resolution of 7,086 × 7,086 pixels. The raw data are monochromatic 8‐bit images in the tagged image file format (TIFF). Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…accounting for sunspots using alternative data, such as white light observations (e.g. Willis et al, 2016;Pal et al, 2020), could allow irradiance reconstructions from properly calibrated historical Ca II K observations, e.g. those from Meudon (Malherbe & Dalmasse, 2019) or Kodaikanal (Chatzistergos et al, 2019c) observatories, to extend the reconstruction back to 1892 (Chatzistergos et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…accounting for sunspots using alternative data, such as white light observations (e.g. Willis et al, 2016;Pal et al, 2020), could allow irradiance reconstructions from properly calibrated historical Ca II K observations, e.g. those from Meudon (Malherbe & Dalmasse, 2019) or Kodaikanal (Chatzistergos et al, 2019c) observatories, to extend the reconstruction back to 1892 (Chatzistergos et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…accounting for sunspots using alternative data, such as white light observations (e.g. Willis et al, 2016;Pal et al, 2020), could allow irradiance reconstructions from properly calibrated historical Ca II K observations, e.g. those from Meudon (Malherbe & Dalmasse, 2019) or Kodaikanal (Chatzistergos et al, 2019c) observatories, to extend the reconstruction back to 1892 (Chatzistergos et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The McIntosh [1990] study showed the importance of context observations and large statistical samples in establishing the crucial characteristics of flare-productive regions. To this end, the digitization of such observations may expand this sample of observations as far back as the 18 th century [See Pal et al, 2020, for a non-exhaustive but informative review of digitization efforts]. Moreover, the study also showed that the association between flare-productivity and active region characteristics is statistical: even though it is clear that the most complex classes are associated with higher flaring rates, flares may occur in simpler regions irrespective of the phase of their evolution.…”
Section: Quantifying the White-light Morphology Of Active Regionsmentioning
confidence: 99%